Yaratıcı Endüstrilerde Eğitim Ve İşgücü İlişkisi: İstanbul Çalışması - Güven, Büşra (Fen Bilimleri Enstitüsü, 2017)
Yaratıcı endüstriler, küreselleşen, sınırların ortadan kalktığı ve mobil iş gücünün giderek yaygınlaştığı ekonomilerde önemli bir role sahiptir. Yüksek katma değere sahip olması ve rekabet edebilirliğinin yüksek olması bu ekonomileri geçtiğimiz yüzyılın sonlarından itibaren ülkelerin politika gündemlerine taşımıştır. 21. yy yaratıcı kapitalizminde bilginin ve yaratıcılığın en önemli ürün olması bu olguların başlıca üretim ve aktarım mekanı olan üniversiteleri hiç olmadığı kadar önemli bir konuma taşımaktadır. Yeni ekonomik coğrafya, işgücü yapısındaki yeni düşünceleri ve gereklilikleri beraberinde getirmektedir. Çok hızlı hareket eden ve dönüşen ekonomik süreçlere üniversitelerin işgücünü yetiştiren kurumlar olarak bu hıza yetişebilir hatta önde gidebiliyor olması beklenmektedir. Yaratıcı endüstrilerde istihdam edilen kişilerin eğitimlerine ilişkin teorik yaklaşımların literatüre yansımaları; yaratıcı endüstri öğrenimi alanların üniversite eğitim içeriklerine dair yapılan araştırmalar şeklinde olmuştur. Yaratıcı endüstrilerde eğitim veren üniversitelerin mezunlarının istihdam edilmesine ilişkin kriterler ve üniversite eğitiminin buna yönelik yapması gerekenler hakkında son dönemde giderek artan bir literatür oluşmuştur. Çalışmanın temel amacı kentsel ekonomilerde yaratıcılığın önemi ve ilişkili olarak yaratıcı işgücünün varlığını sürdürebilmesi kapsamında, eğitim-endüstri ilişkileri açısından konuyu değerlendirmektir. Kentsel ekonomik gelişme içerisinde yaratıcı endüstrilerin önemi ve özellikle endüstri işgücünün durumunu tartışarak, yaratıcı işgücü eğitim ilişkisini, eğitim kurumları, endüstri beklentileri ve işbirlikleri çerçevesinde ortaya koymayı amaçlamaktadır. Türkiye’ de yaratıcı endüstrilere ilişkin ulusal düzeyde veri analizi bulunmamak ile birlikte İstanbul’ un yaratıcı endüstrilerin merkezi olduğunu söylemek mümkündür. Araştırmada seçilen endüstrilerde belirlenen eğitim kurumları ve meslek kuruluşları ile literatür araştırmalarına paralel derinlemesine mülakatlar yapılmıştır. Eğitimdeki genel tutumun öncelikli hedefi endüstri ihtiyacını karşılamaya yönelik olmadığı, bunun nedeninin de endüstrinin mevcut durumuna ilişkin sorunlar olduğu ortaya çıkmıştır. Bu noktada her iki görüşme grubu da öğretim üyelerinin eğitim ve endüstri ilişkileri arasındaki dengeyi çok iyi sağlaması konusunda önemli bir role sahip olduğunu belirtmiştir. Üniversite tarafından eğitim ve endüstri ilişkilerinin geliştirilmesine ilişkin en çok belirtilen sorun yönetimsel engellerin varlığı ve dolayısı ile maddi olanaksızlıklar, bunların getirdiği hızlı hareket edememe ve çağın standartlarına uygun altyapıya erişememe olarak belirlenmiştir. Endüstrilere ilişkin en önemli sorun yaratıcı endüstrilerin; ekonomik değerinin rakamlar ile ifade edilebileceği datalara ilişkin analizlerin olmaması bunun da endüstrinin hukuki ve politik zeminde kabul edilirliğini engellediği ve dolayısıyla endüstrileri geliştirmeye yönelik eğitim ve endüstri işbirliklerinde fonların sağlanamaması olmuştur.

Creative industries have an important role in economies where globalization, borderlessness and mobile workforce are increasingly widespread. These economies, which have high added value and high competitiveness, have moved into countries' policy agendas since the late century. In the 21st century creative capitalism, knowledge and creativity are the most important products, and universities, which are the main production and transfer places of these phenomena, are in an important position. The new economic geography brings with it new considerations and requirements for workforce structure. It is anticipated that as the institutions that raise the labor force of the universities to the economic processes that move and change very rapidly, this speed can reach or even go ahead. Literature reflections on the theoretical approaches to the necessity of educating people employed in creative industries; The creative industry has been in the form of research into the content of university education in areas of learning. A growing literature has recently emerged on the criteria for employing graduates of universities providing education in creative industries, and the contributions of education and industry collaborations. The main aim of the study is to assess the relevance of creativity in urban economies and the relevance of the creative workforce in terms of education-industry relations. The aim of the creative industry is to show the creative workforce educational relationship, education institutions, industry expectations and collaborations, by discussing the situation of the creative industry, especially the industrial workforce, in urban economic development. The approaches developed by the creative class to keep pace with the changing world conditions have made an important contribution to the sustainability of creative industries in cities. The identification of current educational and industrial relations and problems in Istanbul is important to include strategies for resolving these problems in future policies on creative industries that are not yet in a political frame in Istanbul and increasingly in volume. However there is no national data analysis of creative sectors in Turkey, it is possible to say that Istanbul is the center of creative industries. The study consists of five basic parts. The theoretical framework is summarized in the second chapter, the theory of creative class and the urban development in the third chapter through the relation of industrial development and education. The fourth chapter consists of the original field study of the research. Determined in Istanbul; education in the light of interviews with universities and creative industrial professional organizations in creative industries, advertising, architecture, industrial design and graphic design, evaluations of problems in the current situation of industries and education-industry relations. The final section consists of conclusions and recommendations. Interviews with selected educational institutions and professional organizations were conducted in parallel with the theoretical framework. The primary objective of the general attitude in education is not to meet the needs of the industry, but it is also the reason for the current state of the industry. At this point, both groups indicated that the teaching staff played an important role in providing a good balance between education and industry relations. The main problem with the development of educational and industrial relations by the university is the existence of administrative obstacles and therefore the financial impossibility, the inability to move quickly, and the inability to access the infrastructure appropriate to modern standards. The most important problem with the industry is that of the creative industries; Because there is no analysis of the economic value that can be expressed by the figures, there is no legal and political ground. The issues related to the development of educational and industrial relations in universities are covered by their general titles; the existence of administrative obstacles and thus the financial impossibilities, the rapid movements they bring, and the inability to access the infrastructures appropriate to the era standards, the inflexibility, the uniformed education style. Problem areas related to industry; the lack of funding in university collaborations, the weakening of the work quality of the creative workforce in the context of the industry, the blunting of creativity, the use of university collaborations with advertising purposes, the industry in projects with the university there have been shortcomings in establishments that leave the university free of space and define what they want. When problem areas of two different groups are overlapped; the fact that the perspectives on cooperations are not clear from both the university and the industry, the financial impossibilities of developing university-industry interaction and the lack of state funded flow of funds have emerged as barriers to cooperation and hence to the industry. When problem areas of two different groups are combined; The fact that there is no politics to contribute to education and industry relations in an economy that is not defined in the legal grounds of the state has emerged as the greatest obstacle to cooperations and industrial development.
A Istanbul Case Study Of Reciprocal Relationship Bewteen Higher Education And Employment In Creative Industries
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2017
Keywords: Yaratıcı Endüstriler; Yaratıcı Sınıf; Eğitim; İstihdam; İşgücü; İstanbul; Creative Industries; Creative Class; Education; Employment; Labour Force; Istanbul